Legal Liability by Companies for Environmental Pollution - Agus Sandiartha (CV. Publikasi Indonesia, 2026)
A healthy environment is the right of every human being and other living creature, but its sustainability is increasingly threatened by human activities and natural factors. Companies have a significant role and legal responsibility for environmental preservation. This study aims to analyze the forms of corporate legal responsibility for the environment and environmental pollution based on positive Indonesian law. The method used is normative legal research, with an analytical approach of laws and regulations, specifically Law Number 32 of 2009 concerning Environmental Protection and Management and other relevant regulations. The results of the study indicate that corporate legal responsibility is divided into three forms: preventive, compensatory, and rehabilitative. Preventive responsibility emphasizes efforts to prevent environmental damage through good management practices and compliance with regulations; compensatory responsibility includes the obligation to provide compensation to affected parties; while rehabilitative responsibility requires the restoration of damaged environmental conditions and the restoration of ecosystem functions. Law enforcement against environmental pollution is carried out through administrative, civil, and criminal sanctions, with criminal sanctions being applied as a last resort Effective implementation of legal responsibilities not only protects the environment, but also increases corporate accountability, reduces legal risks, and supports environmental sustainability and community well-being.